2019
DOI: 10.32725/jab.2019.008
|View full text |Cite
|
Sign up to set email alerts
|

Methylene blue elicits non-genotoxic H<sub>2</sub>O<sub>2</sub> production and protects brain mitochondria from rotenone toxicity

Abstract: Methylene blue (MB) is a promising compound with a broad range of neuroprotective activity. One of therapeutic effects is the activation of mitochondrial biogenesis via Nrf2/ARE signaling cascade. Probably, mild oxidative stress caused by MB-depended H 2 O 2 production is a trigger for activation of this signaling cascade. So mechanistically, MB can be regarded as prooxidant. We investigated the dose-dependent H 2 O 2 production in intact brain mitochondria and showed the increase in the H 2 O 2 production aft… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
10
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 46 publications
1
10
0
Order By: Relevance
“…When evaluating the results of an in vitro experiment, it was found that the damage to mtDNA obtained after treatment with metribuzin and imidacloprid at a concentration of 200 µM is equivalent to the damage induced by treatment with H 2 O 2 at a concentration of 500 µM (Figure 2A, Table 1). We have previously shown similar results when treating mouse brain mitochondria with 500 µM H 2 O 2 and 1 µM rotenone pesticide, where rotenone caused even slightly more damage than H 2 O 2 [52]. It is believed that mtDNA damage is mainly initiated by ROS [53].…”
Section: Effect Of Metribuzin and Imidacloprid On Potato Mtdna In Vitrosupporting
confidence: 59%
“…When evaluating the results of an in vitro experiment, it was found that the damage to mtDNA obtained after treatment with metribuzin and imidacloprid at a concentration of 200 µM is equivalent to the damage induced by treatment with H 2 O 2 at a concentration of 500 µM (Figure 2A, Table 1). We have previously shown similar results when treating mouse brain mitochondria with 500 µM H 2 O 2 and 1 µM rotenone pesticide, where rotenone caused even slightly more damage than H 2 O 2 [52]. It is believed that mtDNA damage is mainly initiated by ROS [53].…”
Section: Effect Of Metribuzin and Imidacloprid On Potato Mtdna In Vitrosupporting
confidence: 59%
“…The studies in rats have shown that the optimal concentration for the injection is 1 to 4 mg/kg [24,25]. Single injections of 50-100 mg/kg MB suppressed the running wheel behavior [26] but did not cause a genotoxic effect [27]. When MB was taken orally with drinking water, a positive effect was observed in the MB concentration range from 15 to 40 mg/kg/ day [28][29][30].…”
Section: Discussionmentioning
confidence: 99%
“…MB is a nootropic agent that inhibits acetylcholinesterase activity and at large doses also monoamine oxidase, thus increasing the levels of catecholamines and acetylcholine ( Pfaffendorf et al, 1997 ; Ramsay et al, 2007 ; Delport et al, 2017 ). Moreover, MB has an important role in mitochondrial energy through the modulation of respiration; it accepts electrons from NADPH (becoming leukomethylene blue MBH) and transfers them to cytochrome c. Therefore, MB is used to enhance mitochondrial function, acting as an alternative electron carrier in the electron transport chain in the mitochondria ( Wen et al, 2011 ; Gureev et al, 2019 ). MB also stimulates glucose metabolism, increasing glucose uptake and ATP production, providing more cellular energy for a better overall brain function including cognition, mood, and memory ( Atamna et al, 2008 ; Rojas et al, 2012 ; Alda et al, 2017 ; Sonntag et al, 2017 ).…”
Section: Therapeutic Strategiesmentioning
confidence: 99%